Transdisciplinary role of physical and mathematical disciplines in modern natural science and engineering education - V. A. Testov; E. A. Perminov (Russian State Vocational Pedagogical University, 2023)
Introduction. In recent decades, a gradual degradation of mathematics and physics training in schools and universities has begun. Obviously, this has caused a significant decrease in the quality of professional training of students in the conditions of commercialisation and continuous reforms of education, and its chaotic digitalisation. At the same time, modern mathematics and physics have become the leader of the transdisciplinary trend in the natural, engineering, and other sciences of the digital era. The transdisciplinary trend generates a universal methodology capable of solving complex multifactorial interdisciplinary problems of nature and society. As a result of the transdisciplinary trend in science, such scientific fields as cybernetics, general systems theory, catastrophe theory, synergetics, artificial intelligence, big data, etc. have emerged. All these concepts were developed on the basis of the achievements of mathematics and physics over the past 70-80 years, which gave rise to the most unique practical achievements in modern, natural, and technical sciences.Aim. The present research aims to explore transdisciplinarity role of physical and mathematical disciplines in modern natural science and engineering education.Methodology and research methods. The system-based approach was used to analyse the role of mathematical and physical science systems in modern education. The synergetic approach became the basis for the study of the transdisciplinary trend of these systems in historical retrospect. In the methodology of these approaches, an important role was played by the methods of students' holistic scientific worldviews formation, including ideas about the modern picture of the world of mathematics and physics. The authors applied the methods to develop student systems thinking (with its important quality of nonlinearity), which underlies the solution of multifactorial interdisciplinary tasks of their professional activity.Results. The results of the analysis of the transdisciplinary role of physical and mathematical disciplines indicate the fundamental importance of the unique potential of these disciplines in the natural science and engineering education in the era of the computer revolution.Scientific novelty. The authors identified, justified and characterised transdisciplinary ideas and methods (in mathematics and physics), which bring natural and engineering sciences to a higher level of cognition, thus contributing to improving the quality of natural science and engineering training of students at universities using a computer.Practical significance. The research materials emphasise considerable practical importance to implement a transdisciplinary approach in didactics and methods of teaching physical and mathematical disciplines in the system of natural science, and engineering education. The research findings will be of interest to educational theorists and teachers, who conduct professional training of students of natural science and engineering fields and to everyone who is interested in the prosperous future of the educational system.